Comparative analysis of CDR3 length-dependent patterns in VHHs - Zhang, Lu; Yang, Tianyu; Zhang, Yao; Yan, Jiahui; Li, Jiaguo; Xu, Wenfeng; Zhu, Weimin; Wang, Xinhao (Frontiers in Immunology, 2025)
IntroductionVHHs, or nanobodies, are distinguished by their compact size, high stability, and unique ability to selectively target specific epitopes. The CDR3 region in VHHs, which plays a crucial role in antigen binding, exhibits significant diversity and varies among species.MethodThis study systematically examined CDR3 length dependent patterns by analyzing NGS sequences from the PBMCs of Alpacas, Llamas and Bactrians, in conjunction with VHH structure data from the public database.ResultsVHHs from Alpacas and Llamas exhibited similar CDR3 length distributions, while Bactrian VHHs displayed significantly longer but narrower length distribution. Key sequence, structural, and VHH/antigen interaction characteristics correlated with CDR3 length were identified. Specifically, longer CDR3s were associated with a lower net charge, reduced surface hydrophobicity, and enhanced interactions with other VHH regions. Structural analyses revealed that longer CDR3s tended to adopt bent conformations with increased helical and coil structures, whereas shorter CDR3s favored extended conformations and β-sheets. Associations between CDR3 length and amino acid usage patterns within VHH sequences were also observed, including preferences at various sites and in antigen interactions. Notably, species-specific differences were apparent, with Alpaca and Llama VHHs showing more pronounced CDR3 length-dependent patterns than those from Bactrians.DiscussionThese findings highlight the significant impact of CDR3 length on VHH sequence, structure, and antigen interaction characteristics, providing valuable insights for VHH engineering, synthetic library design, and the development of therapeutic nanobodies optimized for targeting diverse epitopes.